Antimicrobial Residues from Animal husbandry in Sewage and Sediment: a systematic review - Ashwani Rawat, Sanjeev Kumar Mandal, Preeti Naval (Revista Electronica de Veterinaria, 2024)
Assessing Antimicrobial residues in a variety of environmental and animal-related conditions, extensive study explores the complex nature of Antimicrobial residues. The collection, consisting of 650 papers, provides a thorough analysis of the levels of antibiotics in soil, water, livestock and products derived from animals. According to the first search until the final article selection, the steps of the systematic review are carefully navigated, as illustrated in the PRISMA flow diagram. The integration of eighteen further sources improves the analysis to expand and offers useful data, which is significant. The study goes more deeply and presents aggregated data on Antimicrobial residues, emphasizing the need of effective synthesis for understanding environmental effects. The research offers a thorough perspective through data summaries and visual aids, assisting in well-informed decision-making. An emphasis on preventing illness is evident in the treatment distribution study across livestock categories, highlighting the necessity for specialized health and production methods. Moreover, determining the sensitivity and resistance to antibiotics in both human and non-human populations is essential for promoting responsible Antimicrobial use and preventing the emergence of resistance. The importance-based categorization of materials improves the research even more by making it simpler to assign resources and set priorities across different categories. In overall, this research offers significant understanding of the intricate terrain around Antimicrobial residues, guiding sustainable management approaches along with public health and environmental protection tactics.